Suboptimal nutritional status of school-age children in Addis Ababa: evidence from the analysis of socioeconomic, environmental, and behavioral factors - Adugna, Yimer Mihretie; Ayelign, Abebe; Zerfu, Taddese Alemu (Frontiers Media, 2024)
Background: School-aged children (6–14 years old) are susceptible to malnutrition and micronutrient deficiencies. Environmental and behavioral factors greatly influence their nutritional status. This study aimed to examine the association between dietary factors and the nutritional status of school-aged children attending public and private schools in Addis Ababa.